Characteristics and Outcomes of Endometriosis at Dr. M. Djamil Padang General Hospital in 2023 - Illahi, Fahrur Rozi; Mondale Saputra; Haviz Yuad (Andalas Obstetrics And Gynecology Journal, 2025)
Background. Endometriosis stands as a prevalent benign gynecological condition. It involves the growth of tissue resembling the endometrium outside the uterus, typically impacting the ovaries and peritoneum. Symptoms commonly include premenstrual discomfort and dysmenorrhea. Objective. Knowing the characteristics and outcomes of endometriosis at Dr. M. Djamil Padang General Hospital for the 2023 period. Method. This study is descriptive research aimed at identifying the characteristics of endometriosis among patients at Dr. M. Djamil Padang General Hospital. Conducted in 2023, the study population initially consisted of 129 endometriosis patients. One year later, follow-up was conducted with 73 patients to assess recurrence. Result. There were more patients of reproductive age (97.7%, totaling 126 individuals) than perimenopausal age. The most common complaints reported by patients seeking treatment were dysmenorrhea (81.4%) and non-menstrual abdominal pain (7.8%). The majority of patients were nulliparous (87.6%), followed by multiparous (7%). In terms of BMI categories, most subjects were classified as normal weight (38%) or obese class I (19.4%). Endometriosis lesions were predominantly located in the internal pelvis, particularly in the ovaries (58.1%). Among patients experiencing infertility, the duration was often ≥5 years (31.8%). Nearly all patients received a three-month course of leuprolide acetate injections (97.3%), with additional therapy involving dienogest tablets for three months in 38.4% of cases. Recurrence of symptoms occurred in only 6.8% of patients, while 6.8% of patients became pregnant following treatment. Conclusion. This study concludes that the incidence of endometriosis is high in women of reproductive age. Providing good education about endometriosis is important in order to reduce the delay in diagnosis of this disease so that it can be treated when the stadium was still mild.